153k views
3 votes
(Picture) MULTIPLYING MONOMIALS AND BINOMIALS

(Picture) MULTIPLYING MONOMIALS AND BINOMIALS-example-1
User Synn
by
4.9k points

1 Answer

4 votes

Answer:

Option C is correct, i.e. 2x² +7x -4.

Explanation:

Given is (2x-1)(x+4)

Applying FOIL method:-

F- multiply First two, O- multiply Outer two, I- multiply Inner two, L- multiply Last two.

So, (2x-1)(x+4) = 2x*x +2x*4 -1*x -1*4

(2x-1)(x+4) = 2x² +8x -1x -4

(2x-1)(x+4) = 2x² +7x -4

Hence, option C is correct, i.e. (2x-1)(x+4) = 2x² +7x -4.

User Koin Arab
by
5.6k points